Non-destructive method to estimate the volume of fruits - Rosli, Muhammad Nashriq; Rosli, Muhammad Afiq Hakimi; Mohd Zulhisam, Muhammad Irfan Syabil; Ng, Set Foong; Mahat, Aishah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Finding the volume of fruits is important for both consumers and sellers. The objective of this innovation idea is to provide a creative non-destructive method to measure the volume of fruit with ellipsoid shape and irregular shape. The steps to derive the volume of fruits are illustrated with examples. There are many advantages and benefits for seller when the volume of fruits is obtained. The volume of fruits plays a crucial role in storage and transportation logistics. By knowing the volume, one can optimize the packaging, stacking, and transportation methods. This helps in minimizing wastage, reducing damage, and utilizing storage and transportation space efficiently. It also aids in determining the required storage capacity and ensuring that the fruits are stored and transported in optimal conditions. As a conclusion, finding the volume of fruits provides valuable information for various stakeholders, including farmers, sellers and consumers. It helps in assessing quality, optimizing storage and transportation.